(untitled) (Ornitología Colombiana, 2021)
In a previous study, we presented evidence that the Henicorhina wood-wren inhabiting the upper slopes of the Sierra Nevada de Santa Marta, H. anachoreta, merits status as a species distinct from the lower elevation taxon, H. bangsi, based on genetic and phenotypic evidence as well as differences in song. Moreover, in a narrow zone of sympatry we found that they showed differential responses to the songs of their own vs. the other form. However, we did not present the differences in plumage and morphometrics in detail and did not make a formal taxonomic recommendation regarding their taxonomic status. We do so here, and present more detailed description of the differences in plumage and morphometrics in support of this recommendation.